The Evidentiary Power of BPOM's Digital Supervision of Illegal Cosmetic Products in Civil Justice Practice - Ranma ma; Baidhowi (Universitas Negeri Semarang, 2026)
This study aims to analyze the digital supervision mechanism carried out by the Food and Drug Supervisory Agency (BPOM), as well as to assess how effective the proof of digital data made by the civil justice process is. As part of empirical juridics, this study uses a study of laws and regulations and interviews with judges and BPOM officials. The results of the study showed that cyber patrols, link takedown requests, and account profiling were used to identify perpetrators and distribution networks. The resulting digital data includes the classification of the breach, the identity of the account, screenshots, URLs, and metadata recorded in the internal electronic system. Based on Law Number 11 of 2008 concerning Electronic Information and Transactions, and its amendments, the data must meet the requirements for validity as electronic evidence. However, its strength in civil justice practice relies heavily on proving that the data is true, consistent, and relevant, as well as judges' beliefs in a mixed evidentiary system. To improve legal certainty and consistency of decisions, this study suggests the establishment of technical guidelines for strengthening digital forensic capacity and electronic evidence.